Between- and within-individual variability of urinary phthalate and alternative plasticizer metabolites in spot, morning void and 24-h pooled urine samples - Bastiaensen, Michiel; Malarvannan, Govindan; Gys, Celine; Ait Bamai, Yu; Araki, Atsuko; Covaci, Adrian (Environmental research, 2020)
Due to international regulations, commonly used phthalates such as di(2-ethylhexyl) phthalate (DEHP) are being replaced by other phthalates, such as di-isononyl phthalate (DINP), and di-isodecyl phthalate (DIDP) and by alternative plasticizers (APs) with similar chemical characteristics, like di(isononyl)cyclohexane-1,2-dicarboxylate (DINCH), di(2-ethylhexyl) terephthalate (DEHTP), or di-(2-ethylhexyl) adipate (DEHA). Urinary concentrations of metabolites are frequently used in the exposure assessment of non-persistent chemicals and for biomonitoring purposes, the intra- and inter-day variability of the metabolites should be known. However, the short-term variability of AP and several phthalate biomarkers has not been investigated yet. In this study, we collected all spot samples from 10 healthy adults for 5 consecutive days and 24h pooled urine on one additional day to investigate the short-term variability of 22 biomarkers of phthalates and APs. Metabolites of DEP, DEHP, DiBP, DnBP, DBzP, DINP and DIDP were found in high detection frequencies, while metabolites of most APs were found in approximately 50% of the samples. The short-term reproducibility of metabolites with diet as primary source (DEHP, DINP, DIDP) was poor (intraclass correlation coefficient – ICC < 0.4), whereas biomarkers of DEP, DnBP, DiBP and BBzP showed good consistency, most likely due to more continuous sources resulting in less between-day variance. ICC values of AP metabolites were similar to those of DEHP, but more studies are required to confirm these findings. Overall, reproducibility improved considerably when values were corrected for urinary dilution and when only morning voids samples were considered. Levels in morning voids samples were consistent for 5 days and comparable to 24-h pooled urine for all metabolites except for OH-MEHTP, sum DINP and sum DIDP, which supports the use of morning voids in human biomonitoring studies. •Every urine sample of 10 individuals was collected over 5 consecutive days.•9 alternative plasticizer and 13 phthalate metabolites in spot, morning void and 24-h pooled urine.•Excellent reproducibility (ICC > 0.70) for MEP, MiBP, MBzP concentrations in morning voids.•Correction for urinary dilution led to better consistency in the ICCs.•Morning voids are good surrogates of short-term exposure except for DINP and DIDP metabolites.